Assets at marriage in rural Ethiopia - Fafchamps, Marcel; Quisumbing, Agnes R. (Elsevier, 2005)
This paper examines the determinants of assets at marriage in rural Ethiopia. We identify and test three separate processes that determine assets brought to marriage: assortative matching; compensating parental transfers at marriage; and strategic behavior by parents. We find ample evidence for the first, none for the second, and some evidence of the third for brides. We also find no evidence of competition for parental assets among siblings. Results suggest that parents do not transfer wealth to children in ways that compensate for marriage market outcomes. Certain parents, however, give more assets to daughters whenever doing so increases the chances of marrying a wealthy groom.